Karakteristik Penyeberangan Pejalan Kaki Pada Lingkungan Sekolah (Studi Kasus Sdn Mekar Jaya 11 Dan Sdn Abadi Jaya 1, Kota Depok) - Pradipta, Arya; Sumabrata, R. Jachrizal (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
Pedestrian in school area has different characteristic rompare to commerce area, industry and officearea. Pedestrian especially students has immeasurable in movemeiit of schoolchild having the characterof and off the cuff is ices unforeseen generates accident, if mixed with vehicle traffic, so that safetyof pedestrian in school area, movement pattern of crossing and level of service of crossing facility ofpedestrian is made by important consideration in planning transportation facilihj especially in schoolarea.Intention of this research analysis is about crosswalk characteristic of pedestrian at school area, so thatas planning and scheme of pedestrian facilities and basic facilities can consider the pedestrian characteristicat school area, on the other hand, this research analyses about movement pattern and crossinglay time of pedestrian which can give information of crosswalk facilihJ h;pe of matching with ZonaSelamat Sekolah ( Z.OSS. .The pedestrian characteristics will be analyzed with microscopic methode. Sighting microscopic isapplied by see behavior of journey happened in each individual. By doing research microscopic henceknowable of characteristic, behavior and movement pattern of pedestrian individually. Researchmicroscopimlly could analyzed journey of pedestrianindividually in position and time, where variable applied is N(pedestrian number), T(time), X and Y(location co-ordinate). Location of observation of this research stays at school area at roadway BahagiaRaya, Depok, precisely stm;s at SDN Mekar Jaya 11 and SDN Abadi Jaya 1.Results of this research expected serve the purpose of one of reference in the relation with planning andscheme of crosswalk facilities in school area. Population applied in this research expected able torepresent is typical behavior of pedestrian in school area.Key Word: pedestrian, microscopic, crosswalk, Zona Selamat Sekolah (Z.OSS)